PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS IKLAN YANG MELANGGAR TATA CARA PERIKLANAN - Laila, Khotbatul (Jurnal Cakrawala Hukum, 2017)
The process of the birth of an ad is a very important process for a product marketing of a company because advertising is the lifeblood of a company. Advertising process is a very important step to determine the success of a company for its products. There are advertising rules agreed by several parties to create ads. The rule is called the advertising code of ethics which states that advertising must be honest, responsible and not contrary to applicable law is very relevant to the articles contained in the Consumer Protection Act. Therefore, the importance of avoiding fraud done by the producers, it is necessary to include information related to the product in order to protect the interests of consumers. In Indonesia, there are no laws that specifically regulate the advertising, making the rules about advertising is still subject to some rules of law. Consumers have a lot of confusion when going to claim compensation related violations of violations in the advertising world because it is still a blurring the person in charge of the violation.